Suicidal tendencies: culture of self-destruction in Ottoman Society - Şenol, Nurullah. (My University, 2003)
The main aim of this thesis is to examine the concept of suicide, which is one of the most common, controversial and multidimensional phenomena in the history of mankind, from a historian's perspective within the framework of nineteenth -twentieth century Ottoman society, especially the post-Tanzimat period, by looking at official and literary sources. In the first part of this study, the Investigation Process of the suicide cases by the state is examined. The questions asked by the officers of the period are traced back and the type of evidence and sources used are determined. By looking at the official documents, that is police and quarantine reports related to suicide cases, the aim of the officers, what they really looked for during the investigation and the methods they applied are considered. The second chapter is about the main reasons and methods of suicide in Ottoman society. In this section, suicide reports and theories about the reasons and methods of the suicide are examined together, and the main motives for suicide and the methods that were used are classified. .In the third chapter, perception of suicide in the Ottoman Empire is dealt with. In this section, the suicide notes and statements, some special cases of suicide and the expressions in the suicide reports and literary works of the time which have suicide as a theme have been examined to define the perception of suicide by the people who committed and who attempted suicide, perception by the state perception of suicide in post-Tanzimat literature has been examined respectively.
Keywords: Suicide -- Turkey -- History -- 19th century.; Suicide in literature.; Suicide.